ANALISIS FRAUD PENTAGON DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dassaad; Riyanti; Tasya Chairunisa (Akuntansi research UGR, 2024)
Fraudulent financial statements is the intentional act of omission or error in the preparation of financial statements, or improper presentation of accounting principles. One theory behind cheating is the pentagonal scam theory. This study aims to analyze the impact of financial targets, financial stability, external pressures, ineffective supervision, nature of the industry, changes in auditors, changes in management and the number of impacts. The CEO frequently appears on fraudulent financial statements, either partially or simultaneously. The type of data used in this study is secondary data. The method used is purposeful sampling. The object of this study is financial information of companies in the field of transportation and logistics listed on the Indonesian Stock Exchange in the period 2018-2022. The data obtained involved 11 transport and logistics companies for 5 years and a total of 55 samples were produced. Analytical techniques used were quantitative analysis, namely descriptive analysis, classical hypothesis testing, multiple linear regression tests and hypothesis testing supported by SPSS and MS programs. Excel. The results show that the variables Financial Target (ROA), Industry Nature (RECEIVED) and Change of Auditor (AUDCANGE) have a positive impact on fraudulent financial reporting, while the Financial Stability Variable (ACHANGE), External Pressures (LEV), Ineffective Supervision (IND), Board Changes (DCCHANGE) and Frequent CEO Photographs (CEOPIC) have no effect on fraudulent financial reporting. At the same time, there are 8 independent variables that affect fraudulent financial reporting.